International trade in services: A scoping study of services trade and estimates of benefits from services trade liberalisation - John Ballingall; John Stephenson (New Zealand Institute of Economic Research (NZIER), 2005)
This is a scoping study. It summarises the dynamics of services trade in the world economy and discusses some of the benefits of services trade liberalisation from a qualitative and quantitative view point. We place particular emphasis on the role and interests of developing and least developed countries in world services trade. The study also provides an overview of services trade in the New Zealand economy, and, in places, highlights aspects of services trade where New Zealand's interests might be pursued through further research. In our study we found that although developed economies dominate world services trade, developing countries, including least developed economies, are rapidly expanding their share of world services trade. Moreover, on most measures developing countries stand to benefit the most from services trade liberalisation.
Keywords: 330; Internationaler Dienstleistungsverkehr; Außenhandelsliberalisierung; Neuseeland; Entwicklungsländer